2006
DOI: 10.1186/ar2070
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-actinin-binding antibodies in relation to systemic lupus erythematosus and lupus nephritis

Abstract: This study investigated the overall clinical impact of anti-α-actinin antibodies in patients with pre-selected autoimmune diseases and in a random group of anti-nuclear antibody (ANA)-positive individuals. The relation of anti-α-actinin antibodies with lupus nephritis and anti-double-stranded DNA (anti-dsDNA) antibodies represented a particular focus for the study. Using a cross-sectional design, the presence of antibodies to α-actinin was studied in selected groups, classified according to the relevant Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…However, the electron-dense deposits that are the sites of autoantibody deposition in lupus-prone NZB/W F1 mice do not co-localise with α-actinin. Three previous clinical studies have looked at anti-α-actinin levels in patients with SLE [ 17 - 19 ]. One study showed that purified anti-dsDNA antibodies from patients with SLE were more likely to cross-react with α-actinin if the patients had nephritis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the electron-dense deposits that are the sites of autoantibody deposition in lupus-prone NZB/W F1 mice do not co-localise with α-actinin. Three previous clinical studies have looked at anti-α-actinin levels in patients with SLE [ 17 - 19 ]. One study showed that purified anti-dsDNA antibodies from patients with SLE were more likely to cross-react with α-actinin if the patients had nephritis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although cross-reactivity with a number of proteins (including laminin and type IV collagen) has been postulated (reviewed in [ 13 ]), the importance of anti-α-actinin antibodies has been particularly stressed in recent years. This emphasis on the possible pathogenic role of anti-α-actinin antibodies has arisen as a result of studies in murine models [ 6 , 16 ] and clinical studies [ 17 - 19 ], although anti-α-actinin antibodies could not be eluted from glomerular deposits in mice with LN [ 20 ]. However, no previous study has compared anti-nucleosome and anti-α-actinin antibody levels in the same patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these antibodies are sensitive and specific for diagnosis of JSLE [ 6 ]. Meanwhile, serum anti-α actin antibody seems to be a reliable biomarker for renal involvement in SLE patients, yet relevant antibody is not found in renal biopsy [ 7 , 8 ]. We previously report that, in SLE patients, simultaneously positivity for anti-dsDNA, anti-nucleosome and anti-histone antibodies by Euroline ANA Profile (IgG) test is significantly relevant with LN onset and activity, and suggestive as a valuable indicator for renal involvement [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-autoimmune (BALB/c) mice immunized with alpha-actinin develop anti-alpha-actinin antibodies and develop immune complex glomerulonephritis and proteinuria [35]. Antibodies binding alpha-actinin have been identified in patients with LN [3638].…”
Section: Autoantibodiesmentioning
confidence: 99%